Rhetorical Analysis of Joe Biden’s Inauguration Address - Nurkhamidah, Neni; Fahira, Raihana Ziani; Ningtyas , Ayu Ratna (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
The inaugural speeches mark the beginning of a new term in office for a community or government leader, such as the president. This reaction must persuade the people to believe in the government and the programs will be enacted. This research aims at finding the rhetorical appeals of President Joe Biden's inaugural address on his inauguration as the 46th President of the United States. The research is based on Aristotle's theory called a rhetorical theory. The resercher employs descriptive qualitative as a methodology to analyze the data from the spoken utterances of the speech. The result shows that Joe Biden uses all of the Aristotelian rhetoric strategies in his inaugural address, which are: ethos, pathos, and logos. The data shows that Joe Biden uses pathos as 55% of his speech, followed by ethos 37%, and logos 8%.. Joe Biden skillfully used and implied Aristotle's rhetorical theory in his inauguration address to engage and build trust with the American people. From the analysis, the researcher has concluded that a good speaker can use all of the three elements of the rhetorical theory and imply them in the speech or writing.